CSC541: Programming Interactive Systems / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2022)
This course is intended to introduce students to interactive system and the user-experience-centered view of software development. Students are required to use suitable approach and technology to design and develop software with usable and interactive user interface. The components that will be covered include human and technology aspects of the HCI. In this course, students will demonstrate their HCI knowledge via assignments that require them to analyze the user interface, designing a user interface, developing an interactive system and thus evaluating it using suitable tools and techniques.